SAKRALITAS SIMBOL TAU-TAU DALAM PELAKSANAAN RITUAL RAMBU SOLO’ DI TORAJA (PRESPEKTIF ALUK TODOLO) - Welem, Theofilus (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2023)
Abstract. The development of the times and the introduction of several new teachings into the Toraja area made many changes, specifically the understanding of symbols in the traditional rituals of the Toraja people, one of which is the tau-tau symbol. Tau-tau is one of the heritage symbols that was previously used by aluk todolo adherents in carrying out the rambu solo’ ritual. This paper will analyze the sacredness of the Tau-tau symbol in the implementation of the solo sign ritual (death ritual) in Toraja from the perspective of aluk todolo. Tau-tau is a sculptural symbol of a work of art made of wood, then carved according to the form or appearance of the deceased person in question. This study uses a qualitative research method that is descriptive in nature. Searching for research information will be carried out through literature studies and also through interviews with several parties who are considered competent and have knowledge about the tau-tau symbol in the implementation of ritual rambu solo’. The theoretical approach will use the theory of sacrality from Micea Eliade. The results of the study show that basically the symbol of tau-tau has a sacred value for the Toraja people who adhere to the original belief of the Toraja people (Aluk todolo), they worship and worship tau-tau, because they believe that dead ancestors will be present in the symbol after going through a series of rituals. or ceremony and turn into a god (membali puang).